2021
DOI: 10.1016/j.amsu.2021.102430
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitude to eye disorders among pediatricians in North Jordan

Abstract: Purpose To assess the general knowledge of and attitude to various common eye conditions in children among pediatricians in north Jordan. Methods This was a descriptive cross-sectional study. An exploratory questionnaire was developed by the research team to collect the necessary qualitative information. Results In total, 48 pediatricians participated in the study. Around two-thirds performed eye examinations in children; however, only 10.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…These participants did not differ in terms of age, gender, and years of experience from the rest of the sample. The findings contradict those found in studies conducted in Kenya, Ethiopia, and Jordan [ 6 , 7 , 10 ], which revealed a low level of knowledge among pediatricians treating red eye. A possible reason may be the training program of pediatricians in Israel as well as the training provided on the job.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These participants did not differ in terms of age, gender, and years of experience from the rest of the sample. The findings contradict those found in studies conducted in Kenya, Ethiopia, and Jordan [ 6 , 7 , 10 ], which revealed a low level of knowledge among pediatricians treating red eye. A possible reason may be the training program of pediatricians in Israel as well as the training provided on the job.…”
Section: Discussioncontrasting
confidence: 99%
“…The current recommendations of pediatric ophthalmologists for the treatment of conjunctivitis begin with eyelid hygiene and cleaning the discharge, use of artificial tears, and monitoring. However, according to the literature [ 6 , 7 ], pediatricians do not often follow this course and tend to prescribe antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conjunctivitis will probably cause a painless red eye, 85.1% of our participants stated inaccurately that it causes painful red eyes. These results are in line with the findings of other studies conducted in Jordan and Kenya [ 8 , 14 ]. In comparison to a study conducted in the United States, in which 55% of the general practitioners were willing to prescribe eye drops or ointments to children with painful red eyes, more than half of our physicians (51.5%) were willing to refer the patient immediately to an ophthalmologist [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In another study, HReH attitudes were far more favourable amongst themselves when they were discussing task sharing as opposed to when they were discussing it with management [ 44 ]. A recent study conducted among paediatricians in Jordan reported satisfactory attitudes regarding eye health and disorders [ 45 ].…”
Section: Discussionmentioning
confidence: 99%